2009
DOI: 10.1029/2009gl038108
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal variability of tropical cyclone landfall in the Philippines from 1902 to 2005

Abstract: A dataset of tropical cyclone landfall numbers in the Philippines (TLP) is created from a combination of historical observation records of the Monthly Bulletins of Philippine Weather Bureau and Joint Warning Typhoon Center best‐track data for the period of 1902 to 2005. Interdecadal variability of TLP is found to be related to different phases of the El Niño/Southern Oscillation (ENSO) and the Pacific Decadal Oscillation (PDO). The annual TLP has an apparent oscillation of about 32 years before 1939 and an osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 24 publications
4
85
0
1
Order By: Relevance
“…This was consistent with a predicted increase in rainfall during this period as per the aforementioned bi-decadal rainfall variation (Dyer and Tyson 1977). Largescale circulation anomalies such as the Pacific-Decadal Oscillation and Atlantic Multidecadal Oscillation have been shown to cause decadal-scale variability in the tracks of tropical cyclones over the Atlantic and Pacific Oceans (Chu 2002, Liu and Chan 2008, Matsuura et al 2003, Kubota and Chan 2009, Goldenberg et al 2001. This happens through forcing of variables important to tropical cyclone tracks such as steering flow (defined to be the weighted average flow between 850 hPa and 200 hPa), moisture availability, SSTs, largescale vorticity as well as vertical wind shear (Chan 1985, Holland 1982, Becker et al 2010.…”
Section: Introductionsupporting
confidence: 65%
“…This was consistent with a predicted increase in rainfall during this period as per the aforementioned bi-decadal rainfall variation (Dyer and Tyson 1977). Largescale circulation anomalies such as the Pacific-Decadal Oscillation and Atlantic Multidecadal Oscillation have been shown to cause decadal-scale variability in the tracks of tropical cyclones over the Atlantic and Pacific Oceans (Chu 2002, Liu and Chan 2008, Matsuura et al 2003, Kubota and Chan 2009, Goldenberg et al 2001. This happens through forcing of variables important to tropical cyclone tracks such as steering flow (defined to be the weighted average flow between 850 hPa and 200 hPa), moisture availability, SSTs, largescale vorticity as well as vertical wind shear (Chan 1985, Holland 1982, Becker et al 2010.…”
Section: Introductionsupporting
confidence: 65%
“…The area most frequently affected by tropical cyclones is that of the North-western Pacific Ocean, and annual TC landfall (TCL) numbers in the Philippines varies from 3.6 to 6.0 in the period between 1902 and 2005 [9], with about half of the world's strongest typhoons measured at landfall over the past 80 years having hit the country [5]. Brand and Blelloch [10] investigated the typhoons that directly hit the Philippines and found that around 50% cross in the October-November period.…”
Section: Characterization and History Of Typhoons In The Philippinesmentioning
confidence: 99%
“…Yumoto and Matsuura, 2001;Matsuura et al, 2003;Ho et al, 2004;Chan, 2005Chan, , 2008Liu and Chan, 2008;Chan and Xu, 2009;Kubota and Chan, 2009;Goh and Chan, 2010;Wang et al, 2010;Yeh et al, 2010), while the tracks of WNP TCs seem to be modulated largely by the location, strength, and extent of the North Pacific subtropical high pressure area. Some studies attribute these variations to alterations in coupled atmosphere-ocean phenomena on similar time scales such as ENSO or Pacific Decadal Oscillation (PDO).…”
Section: Introductionmentioning
confidence: 98%